Population pharmacokinetics and pharmacogenomics of apixaban in Japanese adult patients with atrial fibrillation. (16th April 2018) - Ueshima, Satoshi; Hira, Daiki; Kimura, Yuuma; Fujii, Ryo; Tomitsuka, Chiho; Yamane, Takuya; Tabuchi, Yohei; Ozawa, Tomoya; Itoh, Hideki; Ohno, Seiko; Horie, Minoru; Terada, Tomohiro; et al.
Abstract : Aims: This study aimed to analyse the effects of genetic polymorphisms in drug transporters and metabolizing enzymes, and clinical laboratory data on the pharmacokinetic parameters of apixaban. Methods: Data were collected from 81 Japanese patients with atrial fibrillation. Pharmacogenomic data were stratified by ABCB1, ABCG2 and CYP3A5 polymorphisms. The pharmacokinetic profile of apixaban was described by a one‐compartment model with first‐order absorption. Population pharmacokinetic analysis was conducted using a nonlinear mixed effect modelling (NONMEM™) program. Results: The nonlinear relationship between oral clearance (CL/F) of apixaban and creatinine clearance (Ccr) was observed. The population mean of CL/F for a typical patient (Ccr value of 70 ml min −1 ) with the CYP3A5 *1/*1 and ABCG2 421C/C or C/A genotypes was estimated to be 3.06 l h −1 . When Ccr values were set to the typical value, the population mean of CL/F was 1.52 times higher in patients with the CYP3A5 *1/*1 genotype compared with patients with the CYP3A5 *1/*3 or *3/*3 genotype, while the population mean of CL/F was 1.49 times higher in patients with the ABCG2 421C/C or C/A genotype compared with patients with the ABCG2 421A/A genotype. However, no covariates affected the population mean of the apparent volume of distribution (Vd/F) of apixaban. The population mean of Vd/F was estimated to be 24.7 l. Conclusion: The present study suggests that the ABCG2 421A/A and CYP3A5 *3 genotypes and renal function are intrinsic factors affecting apixaban pharmacokinetics. These findings may provide useful information for precision medicine using apixaban, to avoid the risk of adverse reactions.